TANGGUNGJAWAB KEPOLISIAN NASIONAL TIMOR LESTE TERHADAP TINDAKAN KEKERASAN DALAM RUMAH TANGGA DI KOTA DILI - Alves Silva, Hernanes Delfim (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 6 No 2 (2017), 2017)
Household violence as an internal household issue, public issues are in handle openly through law mechanism. In response to the increasing cases of household violence, the Timor leste government then also formulate it as one of the common offenses in constitution number 7 of 2010 about household violence. This is a research by using empirical law research method, the result found two things, firstly, the special unit for the handling of victim of household violence within the scope of the national police of Timor Leste does not yet have an adequate law basis in regulating its duties and responsibilities, because the authority of the special unit is delegatively derived from the general authority owned by national police investigation agency. Second, even if there is no special law umbrella, the special unit still carries out its duties and responsibilities even if it is inadequate. The absence of special law umbrella and inadequate task and responsibilities of special unit  unsupported by human resources. Kekerasan dalam rumah tangga sebagai persoalan internal rumah tangga semata, persoalan publik ditangani secara terbuka melalui mekanisme hukum. Menyikapi meningkatnya kasus kekerasan dalam rumah tangga, pemerintah Timor Leste juga kemudian merumuskannya sebagai salah satu delik umum dalam Undag-undang Nomor 7 Tahun 2010 tentang Kekerasan Dalam Rumah Tangga. Penelitian dengan menggunakan metode penelitian hukum empirik, hasil menemukan dua hal. Pertama, Unit Khusus Penanganan Korban Kekerasan Dalam Rumah Tangga dalam lingkup Kepolisian Nasional Timor Leste belum memiliki landasan hukum yang memadai dalam mengatur tugas dan tanggungjawabnya, karena kewenangan dimiliki unit khusus secara delegatif sebagai turunan dari kewenangan umum yang dimiliki oleh Badan Investigasi Kepolisian Nasional Timor Leste. Kedua, sekalipun tidak memiliki payung hukum khusus, namun Unit Khusus tetap melaksanakan tugas dan tanggungjawabnya sekalipun tidak memadai. ketiadaan payung hukum khusus, ketidakmemadaian pelaksanaan tugas dan tanggungjawab unit khusus tidak didukung oleh sumberdaya manusia
Keywords: Kata Kunci: Kepolisian, Kekerasan Rumah Tangga, Tanggungjawab